Spiritualitas untuk Kesejahteraan Psikologi pada Pasien Penyakit Kronis - Djuria, Syafrina Arbaani; Gayatri, Dewi; Allenidekania, Allenidekania (Journal of Telenursing (JOTING), 2024)
The purpose of this systematic observation is to analyze the relationship between spirituality and psychological well-being in patients with chronic diseases. The research method is by searching the electronic source databases, namely Science Direct, Springer Link, EBSCO, Proquest, and Wiley Nursing published in 2012-2021 with several keywords, namely (Chronic Disease OR Chronic Disease OR Chronic Condition) AND (Spirituality Aspect OR Spirituality OR Spiritual) AND (Psychological Well-being OR Mental Health OR Psychological Distress OR Psychological Adaptation). The results of the study, based on 7 articles analyzed, found a positive relationship between spirituality and psychological well-being in patients with chronic diseases. The conclusion is that high spirituality can improve the mental health of patients. The application of spiritual care is needed to improve the well-being of all aspects of the patient's life so that it can improve the quality of life. Keywords: Psychological Well-being, Chronic Disease, Spirituality